Egmundella fasciculata Fraser 1940 - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
Egmundella fasciculata Fraser, 1940a Egmundella fasciculata Fraser, 1940a: 577, pl. 32, figs. 4a, b. Syntypes. USNM 43436: USA, North Atlantic Ocean off Martha’s Vineyard, R / V Fish Hawk Sta. 949, 40°03’N, 70°31’W, 23 August 1881, rake dredge, 183 m, several colonies or colony fragments, without gonophores, labelled “ type ”; ethanol. Lectotype, by present designation. USNM 43436: USA, North Atlantic Ocean off Martha’s Vineyard, R / V Fish Hawk Sta. 949, 40°03’N, 70°31’W, 23 August 1881, rake dredge, 183 m, one colony, 2.5 cm high, in fairly good condition, without gonophores, labelled “ type ”; ethanol. Paralectotypes. USNM 1458911: USA, North Atlantic Ocean off Martha’s Vineyard, R / V Fish Hawk Sta. 949, 40°03’N, 70°31’W, 23 August 1881, rake dredge, 183 m, several colonies or colony fragments, up to 2.0 cm high, in from good to poor condition, without gonophores; ethanol. BCPM 976-00289-001: USA, south of Martha's Vineyard, 40°03'N, 70°31'W, 23 August 1881, 183 m, several colony fragments, in poor condition, without gonophores, labelled “co-type”; 60% IPA. Type locality. USA, Massachusetts: edge of continental shelf south of Martha’s Vineyard, 40°03’N, 70°31’W, 183 m (Fraser 1940a). Current status. Valid. Remarks. Fraser’s (1940a) “ type ” of Egmundella fasciculata is currently listed as a holotype in the online database of the NMNH (USNM 43436). However, several colonies or colony fragments were present in the collection. The best of these specimens has been designated as the lectotype (USNM 43436). All others in the series are paralectotypes (USNM 1458911). Also present in this collection, together with the paralectotypes, are specimens of a species of campanularioid. Other material from the same collection, held in the Fraser Hydroid Collection at the RBCM (BCPM 976-00289-001), is labelled a “co-type” of E. fasciculata . Now in poor condition, it likewise constitutes a paralectotype. Egmundella fasciculata is listed as valid by Cairns et al . (2002) and WoRMS. The species is known only from the original ...